Dogmas, challenges, and promises in phase III allergen immunotherapy studies - Pieter-Jan De Kam, PhD; Matthias F. Kramer, MD; Mohamed H. Shamji, PhD; Kemi Oluwayi, MD; Matthew D. Heath, PhD; Erika Jensen-Jarolim, MD; Markus H. Berger, MD; Uwe E. Berger, MBA; Anke Graessel, PhD; Fiona Sellwood; Stefan Zielen, MD; Christian Vogelberg, MD; et al. (World Allergy Organization Journal, 2021)
The concept of treatment of an allergy with the offending allergen was introduced more than a century ago. Allergen immunotherapy (AIT) is the only disease modifying treatment of allergic diseases caused by inhalational allergens and insect venoms. Despite this, only few AIT products have reached licensure in the US or an official marketing authorization status in European countries. Moreover, most of these AIT products are provided on an individual patient basis as named patient products (NPP) in Europe, while individualized preparations of (mixed) allergenic extract vials for subcutaneous administration (compounding) is common practice in the US. AIT products are generally considered safe and well tolerated, but the major practical clinical development challenge is to define the optimal dose and prove the efficacy and safety of these products using state-of-the art Phase II and pivotal Phase III studies. In planning Phase II-III AIT studies, a thorough understanding of the study challenges is essential (e.g. variability and non-validated status of subjective primary endpoints, limitations of pollen season definitions) and dogmas of these products (e.g., for sublingual immunotherapy (SLIT) trials double-blinding conditions cannot be maintained, resulting in stronger placebo responses in the active treatment group and inflated treatment effects in Phase III). There is future promise for more objective biomarker endpoints (e.g. basophil activation (CD63 and CD203c), subsets of regulatory dendritic, T and B cells, IL-10–producing group 2 innate lymphoid cells; alone or in combination) to overcome several of these dogmas and challenges; innovation in AIT clinical trials can only progress with integral biomarker research to complement the traditional endpoints in Phase II-III clinical development. The aim of this paper is to provide an overview of these dogmas, challenges and recommendations based on published data, to facilitate the design of Phase III studies and improve the evidence basis of safe and effective AIT products.